COVID-19 PANDEMIC: ITS EFFECT ON RETAIL BUSINESS GROWTH IN INDONESIA - Abdul Aziz (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to analyze the impact of the COVID-19 pandemic on retail businesses in Indonesia. The research method used is a descriptive qualitative method, using secondary data sources from research results, references and online news related to the research. The COVID-19 pandemic that hit Indonesia caused a significant decline in turnover for the retail business. There are several businesses engaged in the retail trade sector that have to be willing to close because they are no longer able to benefit from their operations. Technological developments in globalization are very influential on the economy, including the retail market. The results of this study indicate that the retail sector is the type of business most affected by the COVID-19 pandemic, including the automotive industry, steel industry, electrical equipment, textile industry, handicrafts and heavy equipment, tourism. Meanwhile, the industries that are able to survive during the COVID-19 pandemic are 1. MSMEs that are able to adapt their business with innovative products. 2. The retail industry is able to survive, this is because some of them take advantage of sales through digital marketing. 3. Other industries that are able to survive during the COVID-19 pandemic are those related to meeting basic needs, including electricity, clean water, agriculture, animal husbandry, plantations, fisheries, automotive and banking. Industries that experienced development during the COVID-19 pandemic were food, pharmaceuticals, information and communication technology.